1996
DOI: 10.1021/bi952687j
|View full text |Cite
|
Sign up to set email alerts
|

Domain Closure in Adenylate Kinase

Abstract: The method of time-resolved dynamic nonradiative excitation energy transfer (ET) was used to analyze the proposed domain closure in adenylate kinase (AK). A highly active mutant of Escherichia coli AK, (C77S, V169W, A55C)-AK, was prepared, in which the solvent- accessible residues valine 169 and alanine 55 were replaced by tryptophan (the donor of excitation energy) and cysteine, respectively. The latter was subsequently labeled with either 5- or 4-acetamidosalicylic acid (the acceptor). From the comparative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
134
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(149 citation statements)
references
References 58 publications
13
134
2
Order By: Relevance
“…The WHAM provides a convenient, statistically based approach to combine trajectory data from multiple windows with their different biasing potentials and obtain the PMF along a reaction coordinate. Here, we use it to calculate the PMF along our selected reaction coordinate, the distance between the mass centers of residues 55 and 169, which are the residues that were labeled in the energy transfer experiments 7 and serve as a monitor of the Amp-bd domain-to-core distance. To make sure of the convergence of the PMF, we calculated the PMF for the time corresponding to the first half and the second half of the trajectory for the DREMA and DREMB data.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The WHAM provides a convenient, statistically based approach to combine trajectory data from multiple windows with their different biasing potentials and obtain the PMF along a reaction coordinate. Here, we use it to calculate the PMF along our selected reaction coordinate, the distance between the mass centers of residues 55 and 169, which are the residues that were labeled in the energy transfer experiments 7 and serve as a monitor of the Amp-bd domain-to-core distance. To make sure of the convergence of the PMF, we calculated the PMF for the time corresponding to the first half and the second half of the trajectory for the DREMA and DREMB data.…”
Section: Resultsmentioning
confidence: 99%
“…5 The importance of domain conformational changes has been emphasized by recent experiments showing that they, versus the chemical, phosphoryl transfer step, are rate limiting in AKE and can rationalize differences in activity between mesophiles and thermophiles. 6 Crystallography 1 and time-resolved dynamic nonradiative excitation energy transfer experiments 7 show that binding AMP is associated with an initial conformational change. Binding of the next substrate, usually modeled with a binary substrate, mimics AP 5 A (ATP and AMP linked by a fifth phosphate group), resulting in the formation of the closed, catalytically competent form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-resolved fluorescence energy transfer studies of fluorescent AKeco derivatives confirmed domain closure in solution upon inhibitor binding (23,24). These studies also indicated that large-amplitude segmental mobility of AMPbd and LID is in effect in the ligand-free form (23). AKeco is the only adenylate kinase for which crystal structures corresponding to the extreme stages of the catalytic cycle are available (17,21,22), with the closed form represented by AKeco*AP 5 A.…”
mentioning
confidence: 85%
“…AK was chosen for this study because many aspects of this enzyme have been studied both experimentally (11)(12)(13)(14)(15)(16)(17)(18)(19) and theoretically (20)(21)(22)(23)(24). It is an ubiquitous enzyme that helps maintain the energy balance in cells by catalyzing the reversible reaction, Mg 2ϩ ⅐ATP ϩ AMP º Mg 2ϩ ⅐ADP ϩ ADP.…”
mentioning
confidence: 99%